Comparison of female rat reproductive effects of pubertal versus adult exposure to known endocrine disruptors - Boberg, Julie; Li, Tianyi; Christiansen, Sofie; Draskau, Monica K.; Damdimopoulou, Pauliina; Svingen, Terje; Johansson, Hanna K. L. (Frontiers in Endocrinology, 2023)
A prevailing challenge when testing chemicals for their potential to cause female reproductive toxicity is the lack of appropriate toxicological test methods. We hypothesized that starting a 28-day in vivo toxicity study already at weaning, instead of in adulthood, would increase the sensitivity to detect endocrine disruptors due to the possibility of including assessment of pubertal onset. We compared the sensitivity of two rat studies using pubertal or adult exposure. We exposed the rats to two well-known human endocrine disruptors, the estrogenic diethylstilbestrol (DES; 0.003, 0.012, 0.048 mg/kg bw/day) and the steroid synthesis inhibitor ketoconazole (KTZ; 3, 12, 48 mg/kg bw/day). Specifically, we addressed the impact on established endocrine-sensitive endpoints including day of vaginal opening (VO), estrous cyclicity, weights of reproductive organs and ovarian histology. After 28 days of exposure, starting either at weaning or at 9 weeks of age, DES exposure altered estrous cyclicity, reduced ovary weight as well as number of antral follicles and corpora lutea. By starting exposure at weaning, we could detect advanced day of VO in DES-exposed animals despite a smaller body weight. Some endpoints were affected mainly with adult exposure, as DES increased liver weights in adulthood only. For KTZ, no effects were seen on time of VO, but adrenal and liver weights were increased in both exposure scenarios, and adult KTZ exposure also stimulated ovarian follicle growth. At first glance, this would indicate that a pubertal exposure scenario would be preferrable as timing of VO may serve as sensitive indicator of endocrine disruption by estrogenic mode of action. However, a higher sensitivity for other endocrine targets may be seen starting exposure in adulthood. Overall, starting a 28-day study at weaning with inclusion of VO assessment would mainly be recommended for substances showing estrogenic potential e.g., in vitro, whereas for other substances an adult exposure scenario may be recommended.